(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2026)
This article is devoted to the history of institutions and organizations that were engaged in the protection and restoration of architectural monuments in our country during the 1920s-1980s. The significance and value of the work carried out within the scope of the competence of restoration organizations in the fate of historical monuments are based on this. Through information on this area, issues such as systematization in the history of restoration, achieved positive results and shortcomings, and the attitude towards cultural monuments in general are analyzed.